INVESTIGATING MEDICAL STUDENTS’ LEARNING OF SPECIALIZED VOCABULARY IN ENGLISH AT TRA VINH UNIVERSITY, VIETNAM - Nguyen Thi Cam, Nhung; Khau Hoang, Anh (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2023)
This study investigated a group of medical students’ perspectives on common difficulties in learning specialized vocabulary in English or English for Specific Purposes in their program. The study employed a quantitative method, which used a five-point Likert scale questionnaire to survey 214 medical students at Tra Vinh University. The study results revealed that as the students realized the importance of the specialized course, they had set clear goals for their studies. In particular, specialized vocabulary in English materials is one of the obstacles that students encounter in their learning process. Besides, the participants admitted that they also faced learning problems due to teaching methods. The study also found that they had difficulties in learning specialized vocabulary due to many problems, such as multi-syllabic words which made them difficult to enunciate, write, memorize, identify meanings, abbreviate terms, and associate collocations. Recommendations for related stakeholders such as the Faculty of Specialization and Foreign Languages were included to improve the learning and teaching of specialized vocabulary in English at Tra Vinh University.